RANGES OF DRUG RESISTANCE OF THE PATHOGEN SENSITIVE TO RIFAMPICIN AND RESISTANT TO ISONIAZID IN PULMONARY TUBERCULOSIS PATIENTS - I. A. Burmistrova; A. G. Samoylova; K. A. Glebov; A. E. Panova; T. S. Radina; I. A. Vasilyeva (Туберкулез и болезни лёгких)
.